(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Instrumental methods for assessing colour fastness of textile products have been standardized by organizations such as the International Organization for Standardization (ISO) and Japanese Industrial Standards (JIS). In addition to these, a few methods have been proposed. Despite the existence of these methods, fastness assessments are still being carried out in many places through visual inspection. In a laboratory, experienced inspectors share a common understanding about degree of fastness; however, there are variations between laboratories across different countries and between experienced workers and trainees. Therefore, in order to encourage the use of the instrumental method, four methods were re- evaluated. In the experiment, a set of fabric samples were instrumentally evaluated using four different methods and the samples were also visually assessed by professional inspectors in a textile testing centre in Japan. Then, the results of the instrumental methods were evaluated by comparing with the visual results. A method proposed by Gui and Luo et al was considered to be the best model in terms of the agreement with the visual results and also this method was less influenced by the difference of colour measurement methods.